Incubation in a Temperate Passerine: Do Environmental Conditions Affect Incubation Period Duration and Hatching Success? - Higgott, Caitlin G.; Evans, Karl L.; Hatchwell, Ben J. (Frontiers in Ecology and Evolution, 2020)
The timing of breeding often has a profound influence on reproductive success in birds living in seasonal environments in which nestling food availability changes rapidly. Timing is typically investigated with reference to lay dates, but the timing of hatching is also influenced by the length of the incubation period, which is likely to depend on both environmental conditions and parental behaviour. The aim of this study was to use a 24-year dataset to investigate the abiotic and biotic factors influencing variation in incubation duration in long-tailed tits (Aegithalos caudatus), a species exhibiting substantial variation in incubation duration. We also assess the consequences of variation in the length of incubation periods for hatching success and the risk of nest predation. We found support for our predictions that later breeding attempts, drier conditions and larger clutches were associated with shorter incubation periods. Larger clutches were also more resilient to increases in incubation duration associated with rainy conditions. Surprisingly, warmer ambient conditions were associated with longer incubation periods. Weather conditions did not influence hatching success suggesting that adverse conditions are buffered by nests or by parental behaviour. We also show that longer incubation periods are likely to be costly, however, due to increased exposure to nest predators, and because longer incubations are associated (albeit weakly) with increased risk of hatching failure.